The living image in the Middle Ages and beyond
1 online resource
Keywords: "This edited volume discusses images that bleed, speak, cry, move and behave in ways we usually attribute to living creatures. Living images have been the object of devotion as well as targets of destruction, and they have been marginalised in both culture and cultural studies for their ambivalence, as well as their transgressive nature. But what is it that makes images the loci of such powerful properties? The present volume is an attempt to recuperate the living image, to draw it from the margins, and re-illuminate its importance for cultural history. The title of this book reflects the ambition of the contributions to navigate between the Middle Ages (of the past) and the Middle Ages of the present. Our aim is to provide new theoretical reflections and methodologies concerning the study of material agency and "living images" both historically and today. Chapters include close examination of surviving objects and archival research, as well as theoretical reflections, and span chronologically and geographically across Europe from North to South. The book will be of interest to scholars working in art history, medieval studies, material culture, theatre studies, and religious history"--